Obtenção de sistemas auto-organizados formados por sais de bile e lecitina: efeito da adição de solutos polares - Zambuzi, Giovana Cristina (Universidade Federal de São Carlos, 2024)
Understanding the physicochemical properties of obtaining aggregates provides insights into how to modify and adjust them for specific applications of interest. Self-aggregated systems can be obtained by adding surfactants above the critical micellar concentration in polar and nonpolar solvents. Lecithin is a mixture of phospholipids consisting of two tails and with a positively and negatively charged head, having a wide application in the pharmaceutical and cosmetic industries. Bile salts are biosurfactants formed by a hydrophilic and a hydrophobic side, being used in food and pharmaceutical technologies. In this context, this work aimed to verify the influence of small amounts of the polymeric and monomeric solutes polyethylene glycol (PEG) (400 g.mol-1) and propylene glycol (PG), respectively, on the formation of bile salt and lecithin aggregates. in organic medium (cyclohexane). In this case, three different bile salts were used, namely sodium taurodeoxycholate (NaTDC), sodium deoxycholate (NaDC) and sodium cholate (NaC) and in three different proportions (0.2; 0.4 and 0.8 Bile salt/Lecithin). Self-aggregated systems were studied by using dynamic light scattering (DLS), rheology and small-angle X-ray scattering (SAXS). The measurements showed that the addition of PEG and PG promoted the formation of cylindrical aggregates (giant micelles) for most systems formed by NaC/Lecithin and NaDC/Lecithin, with the 0.8 NaDC/Lecithin system with PEG or PG being the most viscoelastic, with plateau modulus values, G0, equal to 2.8x104 e 3.6x104 Pa in the presence of PEG and PG, respectively. The results showed the obtaining of micelles with high relaxation time values (τR) equal to 100 and 102 s for 0.2 NaTDC/Lecithin and 0.2 NaTDC/Lecithin/PG, respectively. Furthermore, the persistence lengths of the micelles, lp, were in the range of 17,1 to 20,3 nm, and the aggregates obtained in the presence of PEG were less flexible. Furthermore, the SAXS curves showed that most systems presented the formation of giant micelles and lamellae in the presence of solutes. These results showed that the hydrogen bonds established between the hydroxyl groups of the solutes and the polar groups of the surfactants were responsible for the formation of longer giant micelles and/or longer relaxation times. Thus, the systems formed can be used as drug encapsulation and release platforms for various applications.
Obtaining self-organized systems formed by salts of bile and lecithin: effect of the addition of polar solutes
Keywords: Lecitina; Sal de bile; Polietilenoglicol; Propilenoglicol; Reologia; Agregados; Lecithin; Polyethylene glycol; Propylene glycol; Rheology; Aggregates; Bile salt; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA